Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Guru - Revina Dewi Agustin; Wilda Ulil Ulya; Feni Selfiana; Muhammad Sadam Reyhan; Mu’alimin Mu’alimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Organizational culture and work environment play a significant role in teacher performance in determining direction and success. The combination of the two creates a complex dynamic in teacher performance in schools. The purpose of this study is to reveal the extent to which these two factors interact and influence the quality of teacher performance in schools. This research uses the literature review method from various scientific papers or journals. The results of the literature review show that organizational culture and work environment affect teacher performance, namely an inclusive organizational culture. In addition, there is a significant effect on the work environment on teacher performance, which indicates that the work environment can be one of the factors that influence the improvement of teacher performance in schools. Thus, organizational culture and work environment can improve teacher performance in schools.